Website-Based Digital School Information System UPT SMP Negeri 5 Medan With Agile Scrumban - Sri Wahyuni; Darmeli Nasutioan; Abdul Khaliq (Yayasan Sinergi Multidimensi Kreatif, 2024)
This research aims to design and implement a website-based digital school information system at UPT SMP Negeri 5 Medan. In today's digital era, the need for efficient and effective information systems is essential to support good education management. This information system is designed to facilitate the management of academic, administrative, and communication data between the school, students, and parents. The methods used in this study include literature study, needs analysis, and system development using the Agile approach. The results of the study show that this digital school information system is able to provide important features, such as student data management, grade management, announcements, and communication forums. With this system, it is hoped that it can increase efficiency in information management, speed up the administrative process, and facilitate access to information for all related parties. Evaluation of the system is carried out through trials involving users, which shows a high level of satisfaction and ease of use. This study concludes that the website-based digital school information system at UPT SMP Negeri 5 Medan can be a solution to improve the quality of education management, as well as provide significant benefits for the entire school community. Suggestions for further development are to improve interactive features and provide training for users so that the system can be used to the fullest